Measurement of ablation impulse and direction with oblique laser-pulse irradiation. (June 2023) - Nakamura, Yusuke; Moriyama, Daichi; Isomura, Atsushi; Sasoh, Akihiro
Abstract: In this study, a dual-axis impulse stand, having an elastic pivot with a precision of ±0.07 μNs, was newly developed, and the impulse induced by a laser pulse irradiation with a fluence of 10 J/cm 2 was measured for incidence angles of 0°, 30°, 45°, and 60°. In all cases, the impulse vector was initially directed perpendicularly to the surface of the target. However, as the number of the laser pulse irradiations reached 200, only when the incidence angle was 60°, did the impulse direction shift to the laser-beam direction by approximately 10°. This impulse performance was consistent with the ablation crater morphology consisting in a periodic structure with 100 μm in width and 20 μm in depth, which was observed, through a laser microscope, only at this incidence angle. Highlights: A dual-axis impulse stand, having an elastic pivot with a precision of sub-μNs, was newly developed. A laser-ablation impulse vector with oblique irradiation was investigated with the impulse stand. When the incidence angle was 60°, the vector shifted to the laser-beam direction.